Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt Timexs Indonesia Di Kabupaten Tangerang - Alya Istiana Annisa; Edy Krisyanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of motivation and work discipline on employee performance partially and simultaneously at PT. Timexs Indonesia employees in Tangerang Regency. This study uses a quantitative approach with a survey method. Data were obtained through interviews, questionnaires, and supported by literature studies. Data processing was carried out using SPSS version 29 with analysis techniques in the form of descriptive statistics, data quality tests, classical assumption tests, linear regression analysis, coefficient of determination tests, and hypothesis tests. The research sample consisted of 60 respondents who were all employees of PT. Timexs Indonesia in Tangerang Regency. The results of the study indicate that motivation partially has a positive and significant effect on employee performance with a regression equation of KK = 30.494 + 0.899M, a coefficient of determination of 52.6%, and a t-value ofcount 3,946 > ttable1.672 and a significance of 0.000 < 0.05. Work discipline also has a positive and significant effect on employee performance with a regression equation of KK = 25.669 + 0.897DK, a coefficient of determination of 46.2%, and a t-value ofcount 2,637 > ttable1.672 and a significance of 0.011 < 0.05. Simultaneously, motivation and work discipline have a significant effect on employee performance with the regression equation KK = 17.169 + 0.607M + 0.432DK + ε. This is evidenced by the F valuecount 38,974 > Ftable3.159 and significance 0.000 < 0.05